Measuring sustainable development and green investments in contemporary economies - Mieila, Mihai 1975- (Advances in finance, accounting, and economics (AFAE) book series, 2017)
"This book fulfills some major aspects regarding the measuring of sustainable economics and investments taking into consideration the status of world development. It presents some of the most the controversial aspects in measuring green economics and investments. This book provides some of the newest approaches regarding the measuring green economics practices" --Provided by publisher.